Irrigated and non-irrigated radiofrequency ablation systems and ways of non-irrigated RF systems development - Evtushenko A. V. Aleksey Valerjevich; Evtushenko V. V. Vladimir Valerjevich; Bykov A. N. Aleksandr Nikolaevich; Sergeev V. S. Vladimir Sergeevich; Syryamkin V. I. Vladimir Ivanovich; Kistenev Yu. V. Yury Vladimirovich; Anfinogenova Ya. J. Yana Jonovna; Smyshlyaev K. A. Konstantin Alekseevich; Kurlov I. O. Igor Olegovich (2015, 2015)
Title screen